Ectopic expression of SsPETE2, a plastocyanin from Suaeda salsa, improves plant tolerance to oxidative stress. (March 2018) - Zhou, Xin-Tong; Wang, Fang; Ma, Yin-Ping; Jia, Li-Jia; Liu, Ning; Wang, Hai-Yun; Zhao, Pan; Xia, Gui-Xian; Zhong, Nai-Qin
Highlights: SsPETE2 has a novel function in oxidative stress tolerance. SsPETE2 plays the role of antioxidant by regulating the copper ion homeostasis. SsPETE2 possesses a stronger antioxidant capacity than AtPETEs. Abstract: Accumulating evidence indicates that plant plastocyanin is involved in copper homeostasis, yet the physiological relevance remains elusive. In this study, we found that a plastocyanin gene ( SsPETE2 ) from euhalophyte Suaeda salsa possessed a novel antioxidant function, which was associated with the copper-chelating activity of SsPETE2. In S. salsa, expression of SsPETE2 increased in response to oxidative stress and ectopic expression of SsPETE2 in Arabidopsis enhanced the antioxidant ability of the transgenic plants. SsPETE2 bound Cu ion and alleviated formation of hydroxyl radicals in vitro . Accordingly, SsPETE2 expression lowered the free Cu content that was associated with reduced H2 O2 level under oxidative stress. Arabidopsis pete1 and pete2 mutants showed ROS-sensitive phenotypes that could be restored by expression of SsPETE2 or AtPETEs. In addition, SsPETE2- expressing plants exhibited more potent tolerance to oxidative stress than plants overexpressing AtPETEs, likely owing to the stronger copper-binding activity of SsPETE2 than AtPETEs. Taken together, these results demonstrated that plant PETEs play a novel role in oxidative stress tolerance by regulating Cu homeostasis under stress conditions, and SsPETE2, as an efficient copper-chelating PETE, potentially could be used in crop genetic engineering.